Overcoming Challenges in Qur'an Memorization: The Role of Motivation and Teaching Strategies Practices at Islamic Boarding School - Muhammad Faizal Rabbani; Muhammad Wildan Shohib; Nurul Latifatul Inayati (JIE (Journal of Islamic Education), 2025)
This study aims to examine in depth the efforts of students to overcome obstacles faced in memorizing the Qur'an, analyze teacher strategies in teaching and explore the role of supporters in improving students' memorization of the Qur'an at the Assalaam Modern Islamic Boarding School in Sukoharjo. The researcher used a qualitative method with a phenomenological approach. Data collection techniques through interviews, observation, and documentation. The data sources in this study were several ustadz and ustadzah, as well as several students from the tahfidz program. The study results showed that each student had a different way of memorizing, depending on the method that suited their abilities. The efforts of students to overcome obstacles in memorizing include having a firm and sincere intention, being diligent and patient, istiqomah, having one mushaf to strengthen memorization, tahsin Qur'an, and having a healthy body and mind. The strategies tahfidz teachers apply include tahsin, tahfidz, tasmi', and muraja'ah. A comfortable environment, high motivation, and adequate support facilities influence success in memorizing. There are various inhibiting factors: the influence of outside activities from non-tahfidz students, difficulty dividing time, and lack of concentration. This study is expected to provide valuable insights into improving the effectiveness of teaching Qur'an memorization in Islamic educational institutions. The study results can be used by Islamic boarding school managers to design more effective teaching strategies in the process of memorizing the Qur'an by considering the needs and characteristics of each student. In addition, the importance of motivational support and a conducive learning environment can be a concern for Islamic boarding school administrators to create an atmosphere that supports the teaching and learning process.